2015
DOI: 10.1103/physrevb.92.115410
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructure symmetry and the orientation of the quantum Hall nematic phases

Abstract: Clean two-dimensional electron systems in GaAs/AlGaAs heterostructures exhibit anisotropic collective phases, the quantum Hall nematics, at high Landau level occupancy and low temperatures.An as yet unknown native symmetry-breaking potential consistently orients these phases relative to the crystalline axes of the host material. Here we report an extensive set of measurements examining the role of the structural symmetries of the heterostructure in determining the orientation of the nematics. In single quantum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 30 publications
7
37
0
1
Order By: Relevance
“…Our recent measurements 26 revealed that the ground state at ν = 5/2 undergoes a pressure-driven quantum phase transition from the FQHS to a stripe phase [27][28][29][30][31][32][33][34][35][36][37] . In this experiment the two-dimensional electron gas was not exposed to an in-plane magnetic field or any other externally applied symmetry breaking fields 26 .…”
mentioning
confidence: 97%
“…Our recent measurements 26 revealed that the ground state at ν = 5/2 undergoes a pressure-driven quantum phase transition from the FQHS to a stripe phase [27][28][29][30][31][32][33][34][35][36][37] . In this experiment the two-dimensional electron gas was not exposed to an in-plane magnetic field or any other externally applied symmetry breaking fields 26 .…”
mentioning
confidence: 97%
“…Stripe phases stem from the competition between (long-range) repulsive and (short-range) attractive components of Coulomb interaction and can be viewed as a unidirectional charge density wave consisting of stripe regions with either higher or lower integer filling factors. While native stripes are usually aligned along the 110 crystal direction 12 , what exactly determines such preferred orientation remains a mystery [13][14][15] .…”
mentioning
confidence: 99%
“…Second, we recall that the native stripes align along eitherŷ = 110 (most common scenario) orx = 110 orientation 15,22,23,28 but never otherwise. Moreover, there is strong evidence for the existence of two distinct minima in the native orientation potential along orthogonal directions 23 .…”
mentioning
confidence: 99%
See 2 more Smart Citations